2021
DOI: 10.2196/22575
|View full text |Cite
|
Sign up to set email alerts
|

Participant Engagement in a Transmedia Storytelling Web-Based App Intervention for Mental Health of Latina Women: Qualitative Analysis

Abstract: Background Stigma, fear, and lack of knowledge regarding treatment options or where to get help create delays for Latina women in accessing needed mental health help. Story-based media interventions hold appeal for Latina women. Thus, we drew upon the Social Cognitive Theory by Bandura to create an evidence-based, transmedia storytelling web-based app for mental health called Catalina: Confronting My Emotions to connect Latina women to a curated set of mental health resources. Understanding how Lat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The study populations in Table 2 show the studies mostly targeted adolescents, youths, or older adults. While gender differentiation of the study participants is unreported in some studies, four out of the six studies that reported, used either only females or mostly females as study participants (Heilemann et al, 2017; Moon & Park, 2020; Rincon et al, 2022; Soderlund et al, 2021). Table 2 shows that, where specified, the population groups included immigrant Latinas dealing with anxiety and depression, university students, company workers, dementia patients, military veterans suffering PTSD, grieving youths dealing with parental suicide, and youths in social care with mental health needs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study populations in Table 2 show the studies mostly targeted adolescents, youths, or older adults. While gender differentiation of the study participants is unreported in some studies, four out of the six studies that reported, used either only females or mostly females as study participants (Heilemann et al, 2017; Moon & Park, 2020; Rincon et al, 2022; Soderlund et al, 2021). Table 2 shows that, where specified, the population groups included immigrant Latinas dealing with anxiety and depression, university students, company workers, dementia patients, military veterans suffering PTSD, grieving youths dealing with parental suicide, and youths in social care with mental health needs.…”
Section: Resultsmentioning
confidence: 99%
“…All 14 sources stated the specific problems and/or the rationales that necessitated the digital storytelling studies reported. The summarization of these rationales produced four categories, including: limited research on impact of digital storytelling ([5/14]; Bunnell et al, 2017; Ferrari et al, 2022; Heilemann et al, 2017; Litvin et al, 2020; Moon & Park, 2020), high use of online and digital social networking by target population ([5/14]; Gilliam et al, 2012; Hammond et al, 2021; Park et al, 2021; Rincon et al, 2022; Stargatt et al, 2022), effects of mental health experience ([2/14]; Hagstrom, 2017; Jamerson, 2017); and need to explore and describe a digital storytelling game or app ([2/14]; Consalvo & Phelps, 2020; Soderlund et al, 2021). With 10 out of the 14 reviewed, most sources reported that studies were undertaken because of either limited research on the impact or high use of online and digital social networking for storytelling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative measures allow for an in-depth assessment of behavioral, cognitive, and affective dimensions of engagement. Eight studies used qualitative measures to measure engagement [38,49,50,[60][61][62][63][64]. The use of qualitative data is especially suitable for assessing out-of-session effort and the dynamic change of overall engagement over time [19].…”
Section: Qualitative Datamentioning
confidence: 99%